Peran Manajemen Pendidik dan Tenaga Kependidikan dalam Pengelolaan Konflik Sekolah SMPN 36 Surabaya - Andini, Intan Tri; Siahaan, Dborah Graciana; Windasari, Windasari (Lembaga Yasin AlSys, 2024)
Conflict management is a handling process carried out by a authorities in overcoming and regulating conflicts and finding a way out of the problems that occur. With management in handling conflicts, the parties involved in the conflict can avoid consequences that can harm the parties involved uncontrollably. The purpose of this research is to know the ways and steps taken by educators and education personnel in handling conflicts that occur at SMPN 36 Surabaya. The method used in this research is a qualitative method by conducting interviews, observation and documentation studies. SMPN 36 Surabaya has good management in handling conflicts that can strengthen relationship between, teachers, students, and the community around the school. In this article, the discussion discusses the right conflict management strategy.